Michael Jackson : a psychobiography - Ruiters, Jeremy John (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
In a psychobiography a psychological theory is used as a framework to uncover the story of an individual. The psychobiographical approach to research tends to be underutilised. The result of this is that an important area for the application of psychobiographical theory and the study of completed lives is neglected. The value of psychobiographical studies has been advocated by many scholars in the field of psychobiographical research for the development and testing of theories relating to human development. The subject under investigation in this psychobiography is Michael Jackson. Although much has been written about Jackson, not much of the existing literature adopts a psychological focus. The sampling procedure was purposive, as the subject was deliberately selected. The aim of this research was to explore and describe the life of Jackson through the use of the psychobiographical case method. Life history material in the form of biographies, newspaper articles, documentaries and interviews aided in creating a biographical sketch of Jackson's life. The progression of Jackson's personality development was analysed using Erikson's psychosocial development theory. The data collection and analysis were conducted according to Yin's analytical generalisation which consists of two main strategies: (1) using a theoretical framework as a guide to determine what data are relevant, and (2) developing a matrix as a descriptive framework for organising and integrating the data. Furthermore, the process of data analysis was aided by the use of guidelines prepared by Alexander with Erikson's psychosocial development as the theoretical framework. This research undertaking can be recognised as a positive demonstration of the value of Erikson's psychosocial developmental theory in understanding the process of Michael Jackson's personality development. Recommendations regarding future research that utilises the psychobiographical research design and methodology have been made.
Keywords: Jackson, Michael, 1958-2009; Psychology -- Biographical methods; Psychoanalysis; African American singers -- Biography